Braided Composite System with Haptic Feedback for Teleoperation (2024)
A pneumatic-driven soft robotic actuator made from braided nylon coated with silicone elastomer was created using a new fabrication process, with the aim of providing haptic feedback to the fingers in teleoperation applications. The resulting haptic actuator was designed to be flexible, lightweight, and wearable, offering a comfortable user experience. Through the manipulation of the braiding angle, multiple devices were fabricated, focusing on their effective ness in transmitting haptic sensations to the user’s finger.